If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -5) = 3(x + -8) Reorder the terms: 4(-5 + x) = 3(x + -8) (-5 * 4 + x * 4) = 3(x + -8) (-20 + 4x) = 3(x + -8) Reorder the terms: -20 + 4x = 3(-8 + x) -20 + 4x = (-8 * 3 + x * 3) -20 + 4x = (-24 + 3x) Solving -20 + 4x = -24 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -20 + 4x + -3x = -24 + 3x + -3x Combine like terms: 4x + -3x = 1x -20 + 1x = -24 + 3x + -3x Combine like terms: 3x + -3x = 0 -20 + 1x = -24 + 0 -20 + 1x = -24 Add '20' to each side of the equation. -20 + 20 + 1x = -24 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = -24 + 20 1x = -24 + 20 Combine like terms: -24 + 20 = -4 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| 8x-2(x-8)=6(x+1)+4 | | 2x^6-4x^4+x^2-3=0 | | 2d+5/6d-d-6/8d | | -3n-3n=-18 | | -x=-37 | | 3(h-6)=5(2h+3) | | 18/6+7(8)^2 | | 3y+3(y-4)=7y-3(y-10) | | 24t^2+8t=0 | | 3^3*32+12/4 | | -5(n-10)=4(n-6) | | 6+2(5x-3)=70 | | x^2-3x-0x=0 | | 7-(2x-a)=x | | 3(2x+1)-5x=20 | | 2(2+8x)=116 | | 18=6-X+4(2X+3) | | 85=6(5+b)+7 | | 5(n-3)=10(n+2) | | 6-2x-1=4x+6x-3 | | p(-3)=9x-2 | | -96=8(x-8) | | .5(6x+14)=10 | | 80+25x=5/2 | | 4(6v+4)=208 | | y=2/9(12)+2 | | 5/15=7/2 | | -12(x-6)=4(x+5) | | -8(3+4v)=232 | | 9+9n=27 | | 5(3x-4)+2=12 | | (40/9)+2=y |